A propensity score-adjusted analysis of clinical outcomes after pulmonary valve replacement in tetralogy of Fallot. Issue 9 (1st November 2017) - Bokma, Jouke P; Geva, Tal; Sleeper, Lynn A; Babu Narayan, Sonya V; Wald, Rachel; Hickey, Kelsey; Jansen, Katrijn; Wassall, Rebecca; Lu, Minmin; Gatzoulis, Michael A; Mulder, Barbara JM; Valente, Anne Marie
Abstract : Objective: To determine the association of pulmonary valve replacement (PVR) with death and sustained ventricular tachycardia (VT) in patients with repaired tetralogy of Fallot (rTOF). Methods: Subjects with rTOF and cardiac magnetic resonance from an international registry were included. A PVR propensity score was created to adjust for baseline differences. PVR consensus criteria were predefined as pulmonary regurgitation >25% and ≥2 of the following criteria: right ventricular (RV) end-diastolic volume >160 mL/m 2, RV end-systolic volume >80 mL/m 2, RV ejection fraction (EF) <47%, left ventricular EF <55% and QRS duration >160 ms. The primary outcome included (aborted) death and sustained VT. The secondary outcome included heart failure, non-sustained VT and sustained supraventricular tachycardia. Results: In 977 rTOF subjects (age 26±15 years, 45% PVR, follow-up 5.3±3.1 years), the primary and secondary outcomes occurred in 41 and 88 subjects, respectively. The HR for subjects with versus without PVR (time-varying covariate) was 0.65 (95% CI 0.31 to 1.36; P=0.25) for the primary outcome and 1.43 (95% CI 0.83 to 2.46; P=0.19) for the secondary outcome after adjusting for propensity and other factors. In subjects (n=426) not meeting consensus criteria, the HR for subjects with (n=132) versus without (n=294) PVR was 2.53 (95% CI 0.79 to 8.06; P=0.12) for the primary outcome and 2.31 (95% CI 1.07 to 4.97; P=0.03) for the secondary outcome. Conclusion: In this large multicentre rTOF cohort, PVR was not associated with a reduced rate of death and sustained VT at an average follow-up of 5.3 years. Additionally, there were more events after PVR compared with no PVR in subjects not meeting consensus criteria.